Numerical modeling of magnetic field influence on vertical bridgman crystal growth - Lyubimova, Tatyana Petrovna; Fayzrakhmanova, Irina Sergeevna (Computational Continuum Mechanics, 2008)
This paper is concerned with the influence of a homogeneous high frequency magnetic field on the growth of semiconductor monocrystals. An algorithm for modeling the unsteady process of crystal growth by the vertical Bridgman method under terrestrial conditions is presented. As an example, a germanium doped gallium semiconductor material growing in a graphite ampoule with a flat bottom and of finite thickness is considered. Thermal distribution near the outer lateral wall of the ampoule is specified as a tangent function. The influence of the axial high frequency magnetic field on the flow and heat/mass transfer in the melt and on the solute distribution in the grown crystal is modeled. Calculations show that the high frequency magnetic field suppresses convective flows, the flexure of the crystallization front increases with increasing magnetic field intensity, and the melt mixing becomes weaker.